2001
DOI: 10.1017/s0959270901000363
|View full text |Cite
|
Sign up to set email alerts
|

Eagle Owl Bubo bubo and power line interactions in the Italian Alps

Abstract: We reviewed the importance of power lines as a cause of mortality for Eagle Owl in the Italian Alps. Power lines were the most important cause of unnatural mortality for this species, accounting for over 50% of recorded casualties. The number of reported dead owls tended to be higher in September–October, suggesting an influence on juvenile dispersal. Furthermore, the significance of power lines as a cause of mortality increased over time, being lower in the 1960–1980 period than in 1981–1999. Electrocution, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 3 publications
(3 reference statements)
2
24
0
2
Order By: Relevance
“…Fledgling and adult female raptors often are most susceptible to electrocution (Dawson and Mannan 1994, Harmata et al 2001, Rubinolini et al 2001, and we found similar trends. We also found that juvenile hawks tended to be electrocuted within 250 m of nests, whereas adult hawks tended to be killed beyond that radius.…”
Section: Discussionsupporting
confidence: 79%
“…Fledgling and adult female raptors often are most susceptible to electrocution (Dawson and Mannan 1994, Harmata et al 2001, Rubinolini et al 2001, and we found similar trends. We also found that juvenile hawks tended to be electrocuted within 250 m of nests, whereas adult hawks tended to be killed beyond that radius.…”
Section: Discussionsupporting
confidence: 79%
“…For three species (griffon vulture, golden and Bonelli's eagles) detailed monitoring reports on their distribution and population sizes are periodically carried out, so the available information was of high quality. For the Eurasian eagle owl, the quality of the information differed across the study area, but this species' high sensitivity to electrocution a priori made it a good candidate indicator species (Rubolini et al, 2001;Martínez et al, 2006;Pérez-García et al, 2016).…”
Section: Species Sensitivity Mapmentioning
confidence: 99%
“…Eagle owl seems to be the best mortality indicator in our system because its biological traits (size, abundance, status) and other characteristics, such as hunting behavior, confer this species a high sensitivity to electrocution (Janss, 2000;Rubolini et al, 2001;Sergio et al, 2004;Martínez et al, 2006;Schaub et al, 2010). Moreover, other features may justify its selection as indicator species: e.g., it is easy to detect during field samplings due to its large size and reduced carcasses lost by scavenging (Bevanger, 1998;Ponce et al, 2010), and its population is undergoing large-scale recovery process throughout the Iberian Peninsula (Penteriani and Delgado, 2010).…”
Section: Discussionmentioning
confidence: 99%